Asynchronous poleward migration of the Atlantic subtropical gyres over the past 22,000 years - Pinho, Tainã M. L.; Yang, Hu; Lohmann, Gerrit; Portilho-Ramos, Rodrigo C.; Chiessi, Cristiano M.; Bahr, André; Nürnberg, Dirk; Repschläger, Janne; Shi, Xiaoxu; Tiedemann, Ralf; Mulitza, Stefan (Geophysical research letters, 2025)
By exchanging huge amounts of heat between the tropics and high latitudes, subtropical gyres significantly impact Earth's energy balance. Yet, their dynamical changes during the last deglaciation remain poorly understood. Here, nine records of the planktonic foraminiferal species Globorotalia truncatulinoides, that inhabits the permanent deep thermocline of subtropical gyres, are used to explore the meridional migration of both the North and South Atlantic subtropical gyres (NASG and SASG, respectively) in the past 22,000 years. We find that both gyres migrated poleward, with the SASG migration 1,500 years earlier than the NASG. Records from the North Atlantic Ocean indicate that the NASG's northern boundary has shifted over 6°. Climate model simulations suggest that these migrations are coupled with shifts in meridional temperature gradients. The poleward migration of the Atlantic subtropical gyres was crucial for sustaining a milder modern high-latitude climate in comparison with that of the last ice age.